Evaluating teachers' professional development initiatives: towards an extended evaluative framework. Issue 2 (15th March 2018) - Merchie, Emmelien; Tuytens, Melissa; Devos, Geert; Vanderlinde, Ruben
Abstract: Evaluating teachers' professional development initiatives (PDI) is one of the main challenges for the teacher professionalisation field. Although different studies have focused on the effectiveness of PDI, the obtained effects and evaluative methods have been found to be widely divergent. By means of a narrative review, this study provides an extended framework to guide the evaluation of (the effectiveness of) PDI. Furthermore, and in accordance with this framework, an overview of measurement instruments that are currently in use is provided. The study concludes with implications for educational research and developers of PDI.